Description of an Academic-Community Partnership Lifestyle Program for Lower-Income, Minority Adults at Risk for Diabetes - Delgadillo, Adriana T. (2010)
PURPOSE: Translating strategies and approaches from the successful clinically-based Diabetes Prevention Program's lifestyle intervention to community settings is a key next step. This article describes a lifestyle program developed in partnership by researchers at a major university and public health professionals at a local health department. METHODS: The Live Well, Be Well (LWBW) program was designed to meet the needs of lower-income, minority, and low-literacy adults at risk for diabetes. It was adapted from interventions with demonstrated efficacy and delivered in Spanish and English by health department staff. The program consisted of a 6-month active phase and a 6-month maintenance phase and was primarily telephone-based, with one in-person planning session and several group workshops. In-person and group sessions were held in convenient community-based settings. Counselors provided education and skills training to modify diet and increase physical activity. Self-selected and attainable goal-setting and action plans were emphasized to enhance self-efficacy. LWBW is the intervention component of a randomized trial with primary outcomes of fasting glucose, weight, and other clinical measures. CONCLUSIONS: The program provides a unique translational model for implementing diabetes risk reduction programs for underserved populations. Individually-tailored and non-prescriptive, it utilized existing health department infrastructure, focused on telephone counseling, used culturally-appropriate, low-literacy materials, and was delivered in local, community-based facilities.